2010
DOI: 10.3354/ame01396
|View full text |Cite
|
Sign up to set email alerts
|

CO2 and phosphate availability control the toxicity of the harmful bloom dinoflagellate Karlodinium veneficum

Abstract: We demonstrated that the toxicity of the harmful bloom dinoflagellate Karlodinium veneficum is regulated by both CO 2 concentrations and phosphate availability. Semi-continuous cultures were grown in a factorial experiment under all combinations of 3 CO 2 levels (230, 430 and 745 ppm) and 2 phosphate conditions (0.5 and 20 µM). After steady-state acclimation was achieved, karlotoxin cellular quotas and growth rates were determined in all 6 treatments. This strain produced both types of karlotoxin, KmTx-1 and K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 52 publications
(52 reference statements)
2
77
2
Order By: Relevance
“…Recent study has shown that the dinoflagellate Alexandrium ostenfeldii, a common (although typically not bloom forming) species in the central Baltic Sea, produces higher levels of saxitoxin under elevated pCO 2 (Kremp et al unpublished results). Similar results for other dinoflagellates have been found in other parts of the world (Fu et al 2010). No study has yet been done on the effects of increased pCO 2 on the common toxic bloom-forming dinoflagellates in the Baltic Sea, although these findings herald the possibility that nearfuture climate change may increase the toxicity of at least some of the algal blooms in the Baltic Sea.…”
Section: Primary Producerssupporting
confidence: 71%
“…Recent study has shown that the dinoflagellate Alexandrium ostenfeldii, a common (although typically not bloom forming) species in the central Baltic Sea, produces higher levels of saxitoxin under elevated pCO 2 (Kremp et al unpublished results). Similar results for other dinoflagellates have been found in other parts of the world (Fu et al 2010). No study has yet been done on the effects of increased pCO 2 on the common toxic bloom-forming dinoflagellates in the Baltic Sea, although these findings herald the possibility that nearfuture climate change may increase the toxicity of at least some of the algal blooms in the Baltic Sea.…”
Section: Primary Producerssupporting
confidence: 71%
“…Similarly, silica-and P-limitation increases cell quotas of the neurotoxin domoic acid in the diatom Pseudo-nitzschia multiseries (Pan and Rao, 1996;Pan et al, 1998;Sun et al, 2011). In addition, N-and Plimitation increases cellular karlotoxins by 2-to 15-fold in the dinoflagellate Karlodinium veneficum, which has caused fish-killing blooms (Adolf et al, 2009;Fu et al, 2010) and P-limitation causes over 10-fold increases in cell quotas of the toxin nodularin in the Nfixing cynaobacterium Nodularia spumigena, which has formed massive blooms in the Baltic Sea (Sunda et al, 2006). Thus, while our current model was constructed for Karenia brevis, similar positive feedback models should also apply to many other bloomforming, toxic species.…”
Section: Model Generalization and Assumptionsmentioning
confidence: 99%
“…Increased temperatures are thought to trigger proliferation of these harmful algae. While there are few studies investigate the potential impact of ocean acidification on the HABs, it has been recently demonstrated that CO 2 combined with limited nutrient enhanced karlotoxin and domoic acid production by Karlodinium veneficum (Fu et al, 2010) and Pseudonitzschia fraudulenta (Tatters et al, 2012), respectively. Ocean acidification and warming will occur in a background of chronic contamination of the coastal area through human discharges of contaminants.…”
Section: Combined Impact With Toxicantsmentioning
confidence: 99%